BRI1 EMS SUPPRESSOR1 genes regulate abiotic stress and anther development in wheat (Triticum aestivum L.) - Wang, Dezhou; Zuo, Jinghong; Liu, Shan; Wang, Weiwei; Lu, Qing; Hao, Xiaocong; Fang, Zhaofeng; Liang, Ting; Sun, Yue; Guo, Chunman; Zhao, Changping; Tang, Yimiao (Frontiers in Plant Science, 2023)
BRI1 EMS SUPPRESSOR1 (BES1) family members are crucial downstream regulators that positively mediate brassinosteroid signaling, playing vital roles in the regulation of plant stress responses and anther development in Arabidopsis. Importantly, the expression profiles of wheat (Triticum aestivum L.) BES1 genes have not been analyzed comprehensively and systematically in response to abiotic stress or during anther development. In this study, we identified 23 BES1-like genes in common wheat, which were unevenly distributed on 17 out of 21 wheat chromosomes. Phylogenetic analysis clustered the BES1 genes into four major clades; moreover, TaBES1-3A2, TaBES1-3B2 and TaBES1-3D2 belonged to the same clade as Arabidopsis BES1/BZR1 HOMOLOG3 (BEH3) and BEH4, which participate in anther development. The expression levels of 23 wheat BES1 genes were assessed using real-time quantitative PCR under various abiotic stress conditions (drought, salt, heat, and cold), and we found that most TaBES1-like genes were downregulated under abiotic stress, particularly during drought stress. We therefore used drought-tolerant and drought-sensitive wheat cultivars to explore TaBES1 expression patterns under drought stress. TaBES1-3B2 and TaBES1-3D2 expression was high in drought-tolerant cultivars but substantially repressed in drought-sensitive cultivars, while TaBES1-6D presented an opposite pattern. Among genes preferentially expressed in anthers, TaBES1-3B2 and TaBES1-3D2 expression was substantially downregulated in thermosensitive genic male-sterile wheat lines compared to common wheat cultivar under sterile conditions, while we detected no obvious differences under fertile conditions. This result suggests that TaBES1-3B2 and TaBES1-3D2 might not only play roles in regulating drought tolerance, but also participate in low temperature-induced male sterility.